2015
DOI: 10.1371/journal.pone.0122503
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Testosterone Replacement Exerts Cardioprotection against Cardiac Ischemia-Reperfusion Injury by Attenuating Mitochondrial Dysfunction in Testosterone-Deprived Rats

Abstract: BackgroundAlthough testosterone deficiency is associated with increased risks of heart disease, the benefits of testosterone therapy are controversial. Moreover, current understanding on the cardiac effect of testosterone during cardiac ischemia-reperfusion (I/R) periods is unclear. We tested the hypothesis that testosterone replacement attenuates the impairment of left ventricular (LV) function and heart rate variability (HRV), and reduces the infarct size and arrhythmias caused by I/R injury in orchiectomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 54 publications
2
50
0
1
Order By: Relevance
“…The weight loss found in NDO rats could be due to decreased food intake. This finding is consistent with previous studies, which reported that an orchiectomy could cause permanent hypophagia (Gentry & Wade 1976), an increase in oxidative stress (Pongkan et al 2015), and an increase in leptin (Baumgartner et al 1999). The possible mechanism for this could be due to the induction of proinflammatory cytokines (via nuclear factor-κ-B signaling molecules) causing oxidative stress (Vlantis & Pasparakis 2010).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The weight loss found in NDO rats could be due to decreased food intake. This finding is consistent with previous studies, which reported that an orchiectomy could cause permanent hypophagia (Gentry & Wade 1976), an increase in oxidative stress (Pongkan et al 2015), and an increase in leptin (Baumgartner et al 1999). The possible mechanism for this could be due to the induction of proinflammatory cytokines (via nuclear factor-κ-B signaling molecules) causing oxidative stress (Vlantis & Pasparakis 2010).…”
Section: Discussionsupporting
confidence: 92%
“…The possible mechanism could be due to the increasing level of plasma and cardiac MDA, and increased cardiac mitochondrial ROS production in HFO rats. The increase in the level of oxidative stress in the heart may have aggravated an apoptotic pathway (Zorov et al 2006) and led to a decrease in anti-apoptotic (BCL2) levels, and an increase in pro-apoptotic protein (BAX) levels (Pongkan et al 2015), therefore, leading to cardiomyocyte apoptosis and finally LV dysfunction (Aon et al 2009). …”
Section: Metabolic Disturbancementioning
confidence: 99%
See 2 more Smart Citations
“…Orchiectomy was performed using the method described in previous studies (Dulisch 1976, Pongkan et al 2015.…”
Section: Orchiectomy Proceduresmentioning
confidence: 99%